Proximity of brain infarcts to regions of endogenous neurogenesis and involvement of striatum in ischaemic stroke. Issue 3 (11th October 2012) - Delavaran, H.; Sjunnesson, H.; Arvidsson, A.; Lindvall, O.; Norrving, B.; van Westen, D.; Kokaia, Z.; Lindgren, A.
Abstract : Background and purpose: Clinical stroke trials with stem cell‐based approaches aiming for trophic actions, modulation of inflammation and neuroprotection are ongoing. However, experimental studies also suggest that neuronal replacement by grafted neural stem cells (NSCs) and possibly by endogenous NSCs from the subventricular zone (SVZ) may restore function in the stroke‐damaged striatum. To evaluate the potential clinical impact of these findings, we analyzed the spatial relationship of infarcts to the SVZ and the proportion of individuals with striatal lesions in a consecutive series of ischaemic stroke patients. Methods: Patients aged 20–75 years with first‐ever ischaemic stroke underwent DW‐MRI of the brain within 4 days after stroke onset. We analyzed location, size, number of acute focal ischaemic abnormalities and their spatial relationship to the SVZ. Stroke severity was assessed using NIH Stroke Scale (NIHSS). Results: Of 108 included patients, the distance from the nearest margin of the infarct(s) to the SVZ was ≤2 mm in 51/102 patients with visible ischaemic lesions on DW‐MRI. Twenty‐four patients had involvement of striatum. Eight of these had predominantly striatal lesions, that is >50% of the total ischaemic lesion volume was located in caudate nucleus and/or putamen. These 8 patients had a median NIHSS of 3. Conclusions: Many stroke patients have infarcts located close to the SVZ, providing some supportive evidence that optimized endogenous neurogenesis may have therapeutic potential. However, predominantly striatal infarcts are rare and tend to give mild neurological deficits, indicating that striatum should not be the primary target for neuronal replacement efforts in humans.